Gastrointestinal myofibroblasts: role in regulation of physiological activity and reparation of gastro-intestinal tract - E. F. Barinov; O. N. Sulayeva (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
The aim of review. To analyze organ-specific features of gastrointestinal myofibroblasts, functional properties, role in embryogenesis and healing of ulcers of gastro-intestinal tract (GIT).Original positions. Morphology, markers, origin and stimulators of development of myofibroblasts, their involvement in formation of microniche for epithelial stem cells, kinetics of tegmental epithelium, angiogenesis, control of vascular permeability is discussed. Thesefunctions are related to wide spectrum of myofibroblast secretory products, producing molecules of basal membrane, components of matrix and growth factors. Intestinal myofibroblasts are pacemakers for smooth myocytes of GIT, they modulate neurotransmission, participate in modulation of immune response, playing a critical role in reparation of erosions and ulcers of GIT.